Keabsahan Pencatatan Perkawinan Beda Agama Antar Warga Negara Indonesia yang Dilakukan di Luar Negeri - Afifah, Dashilfa; Pranitiaz, Laras Medina; Dewanti, Tyur Regina; Sukma, Nina Fitria; Naufal, Abyan Hafizd; Ramadhani, Dwi Aryanti (Media Hukum Indonesia (MHI), 2024)
This research aims to assess the validity of interfaith marriages between Indonesian citizens conducted abroad based on Law Number 1 Year 1974 on Marriage. In addition, this study also evaluates whether interfaith marriages between Indonesian citizens abroad can be considered as a form of legal smuggling in the perspective of International Civil Law. The approach used is normative juridical research, which utilizes secondary legal sources, consisting of primary, secondary, and tertiary legal materials. The data collection method is done through literature study. Based on the results of the research, it is found that interfaith marriages between Indonesian citizens abroad are considered invalid according to the UUP because they violate the provisions of Article 2 paragraph (1), which states that marriage is valid if it is carried out according to the laws of each religion and belief. Therefore, such interfaith couples often use Article 56 as a basis to solemnize marriages abroad and then record them in Indonesia in order to fulfill administrative requirements in accordance with the UUP. According to the rules of International Civil Law, a marriage is performed under the law of the place where the marriage takes place. However, in the context of Indonesian law, this practice is often considered a form of legal smuggling against Article 2 paragraph (1) of the UUP, as couples avoid the restrictions of national law by marrying abroad. Thus, although legally valid in the country where the marriage was performed, the interfaith marriage is not recognized as valid under the UUP without re-registration in Indonesia.